1986
DOI: 10.1017/s0022029900024869
|View full text |Cite
|
Sign up to set email alerts
|

Heat stability of plasmin (milk proteinase) and plasminogen

Abstract: The effect of heating on plasmin activity in various media, including phosphate buffer pH 7-0, skim milk, blood plasma, solutions of casein and solutions of whey proteins were investigated. Plots of log residual activity v. heating time were linear at all temperatures from 63 to 143 °C. In buffer solutions the presence of casein led to substantial substrate protection, the Arrhenius plots being linear both in the presence and absence of casein. The activation energy, E a , for the inactivation reaction, was 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 24 publications
(33 reference statements)
5
52
0
1
Order By: Relevance
“…This observation is likely due to the denaturation of whey proteins at high temperatures, specifically β-lactoglobulin [21]. The unfolding of β-lactoglobulin exposes a free sulfhydryl group that binds to PL and PG via sulfhydryl/disulfide interchanges, thus rendering it inactive, which has been demonstrated by several authors [1,18,26]. The addition of cysteine decreased PL and PGderived activities without higher heat treatments, as in the LH fluid milk and NFDM, because cysteine initiates thiol-disulfide interchange reactions, resulting in polymerization of PG or binding of PL and PG with other free sulfhydryls in milk proteins.…”
Section: Study 1: Comparison Of Liquid and Non-fat Dry Milkmentioning
confidence: 80%
“…This observation is likely due to the denaturation of whey proteins at high temperatures, specifically β-lactoglobulin [21]. The unfolding of β-lactoglobulin exposes a free sulfhydryl group that binds to PL and PG via sulfhydryl/disulfide interchanges, thus rendering it inactive, which has been demonstrated by several authors [1,18,26]. The addition of cysteine decreased PL and PGderived activities without higher heat treatments, as in the LH fluid milk and NFDM, because cysteine initiates thiol-disulfide interchange reactions, resulting in polymerization of PG or binding of PL and PG with other free sulfhydryls in milk proteins.…”
Section: Study 1: Comparison Of Liquid and Non-fat Dry Milkmentioning
confidence: 80%
“…The results concerning the effects of milk proteins on plasmin stability are similar to previous observations on the heat inactivation mechanism of plasmin. Specifically, several studies have reported significant protection of plasmin in the presence of sodium caseinate, and enhanced inactivation in the presence of β-lactoglobulin [1,22,29]. Heat inactivation of plasmin in the presence of β-lactoglobulin is thought to be linked to the formation of thiol-disulphide bonds with unfolded β-lactoglobulin [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Casein in milk increases the thermal stability of plasmin [1]. The mechanisms and kinetics of thermal inactivation of plasmin have been extensively studied [1,16,22].…”
Section: Introductionmentioning
confidence: 99%
“…Minus and plus symbols indicate an inhibition and an activation, respectively. Question marks indicate that the relationship is suspected but not clearly demonstrated 30% to 40% of plasmin activity can be detected in the milk (Alichanidis et al 1986). Proteolysis of β-casein by plasmin has been shown to play a role in cheese flavor enhancement (Farkye and Landkammer 1992;Farkye and Fox 1992).…”
Section: Plasmin Increase During Mastitismentioning
confidence: 99%